Answer:
Number 3 has no solution
Step-by-step explanation:
First you need to divide both sides of the equation 12x - 12y = -12 by 4
-3x + 3y = -3
12x - 12y = -12
-3x + 3y = -3
3x - 3y = -3
Then you need to eliminate one variable by adding the equations.
0 = -6
this statement is false, and therefore has no solution.
we have that
*-------------------------*--------------------------------*
E F G
EF=2x-12
FG= 3x-15
EG=23
we know that
EF + FG = EG
so
[2x - 12] + [3x - 15] = 23 simplify
5x - 27 = 23 add 27 to both sides
5x = 50 divide both sides by 5
x = 10
EF=2x-12-------> EF=2*10-12-------> EF=8
FG= 3x-15------> FG=3*10-15------> FG=15
therefore
the answer part a) is
the value of x is 10
the answer part b) is
the value of EF is 8
the answer part c) is
the value of FG is 15
The answer is 1/(x+4)
Explanation:
You would factor out the denominator
So,
(X-4)(x+4)=x^2-16
So, x-4/(x+4)(x-4)
Then x-4 cancels each other out from the numerator and denominator
Leaving 1/x+4
If Gap sells jeans that cost $21.00 for selling price of $29.95. The percent of markup based on cost is approximately 43%. The markup in price is exactly $8.95.
Answer:
quadrant 3
Step-by-step explanation: